Substantiation of the effectiveness of various materials for the treatment of pulpitis of deciduous teeth - O. L. Shevchenko; A. A. Antonova (Эндодонтия Today, 2020)
Aim. The purpose is to justify the effective and safe use of various materials for the treatment of pulpitis of temporary teeth by amputation methods. Materials and methods. A retrospective analysis of patient records and treatment of pulpitis of temporary teeth in children by vital amputation was carried out. In order to reveal the pathogenic mechanisms of the development of pulpitis of temporary teeth, the study of oral fluid: the content of immunoglobulins – IgA, IgG, IgM, IgE, sIgA and interleukin–6. Low efficiency – 54.2±0.7% of the method of devital amputation, accompanied by the development of destructive forms of periodontitis was revealed. The most effective method of treatment of pulpitis of temporary molars is the method of vital amputation using the material "Trioxident" – 93,4±0,3 %, "Viscostat" – 91,3±0,4 % with reasonable safety. This allows them to be widely used in children's dental practice.Results. It was shown the high efficiency of the use of drugs "Trioxident" and "Viscostat" in comparison with devital pulpotomy.